‘Churros’ Product Innovation With Sweet Potato - Muhammad Nawawi; Febrianur Febrianur; Annisa Indah Permata; Indah Lestari (EQUATOR SINAR AKADEMIA, 2022)
The natural resources and human resources of the Sukalaksana village are very potential. This condition is why the Sukalaksana sub-district is one of the economically independent villages supported by various agricultural products. This community empowerment and training program aims to develop sweet potato processed products into churros food products that have better-added value and can make the community have a prosperous independent economy, especially for residents of Sukalaksana Village, Curug District, Serang City. After this program was implemented, the results obtained were the development of processed sweet potato products into more innovative churros. The surrounding community better understood the product flow from upstream to downstream by utilizing the potential around the environment.